Contribución al conocimiento de las desmidiáceas del Parque Nacional Los Alerces (Chubut) 2 - Gayoso, Ana María (1976)
In this second part, four species of Euàstrum Ehrenb. and fifteen species of Cosmarium Corda, found in Parque Nacional Los Alerces, Chubut Province, are described. Seven of these species are mentioned for the first time for the Argentine Flore.